Regulation of Carotenoid Biosynthesis by Shade Relies on Specific Subsets of Antagonistic Transcription Factors and Cofactors. Issue 3 (16th June 2015) - Bou-Torrent, Jordi; Toledo-Ortiz, Gabriela; Ortiz-Alcaide, Miriam; Cifuentes-Esquivel, Nicolas; Halliday, Karen J.; Martinez-García, Jaime F.; Rodriguez-Concepcion, Manuel
Abstract : Carotenoid biosynthesis is regulated by plant proximity (shade) signals through specific sets of positive and negative transcriptional regulators targeting the first gene of the pathway. Abstract: Carotenoids are photosynthetic pigments essential for the protection against excess light. During deetiolation, their production is regulated by a dynamic repression-activation module formed by PHYTOCHROME-INTERACTING FACTOR1 (PIF1) and LONG HYPOCOTYL5 (HY5). These transcription factors directly and oppositely control the expression of the gene encoding PHYTOENE SYNTHASE (PSY), the first and main rate-determining enzyme of the carotenoid pathway. Antagonistic modules also regulate the responses of deetiolated plants to vegetation proximity and shade (i.e. to the perception of far-red light-enriched light filtered through or reflected from neighboring plants). These responses, aimed to adapt to eventual shading from plant competitors, include a reduced accumulation of carotenoids. Here, we show that PIF1 and related photolabile PIFs (but not photostable PIF7) promote the shade-triggered decrease in carotenoid accumulation. While HY5 does not appear to be required for this process, other known PIF antagonists were found to modulate the expression of the Arabidopsis ( Arabidopsis thaliana ) PSY gene and the biosynthesis of carotenoids early after exposure to shade. In particular, PHYTOCHROME-RAPIDLY REGULATED1, a transcriptional cofactor that prevents the binding of true transcription factors to their target promoters, was found to interact with PIF1 and hence directly induce PSY expression. By contrast, a change in the levels of the transcriptional cofactor LONG HYPOCOTYL IN FAR RED1, which also binds to PIF1 and other PIFs to regulate shade-related elongation responses, did not impact PSY expression or carotenoid accumulation. Our data suggest that the fine-regulation of carotenoid biosynthesis in response to shade relies on specific modules of antagonistic transcriptional factors and cofactors.